The role of international organizations in developing international law for the environment: an analytical study - Dehaish, Hesham AbdulMalik (Journal of Economic, Administrative and Legal Sciences, 2022)
This article aimed at demonstrate that the traditional interpretation of the sources of international law, which relies on the trio of official sources in Article 38(1) of the ICJ legislation, as well as the clear division between binding and soft law, which still dominates the debate, cannot To define the nature of law-making at the institutional level. This is particularly true in the field of the environment, as scientific skepticism and the unwillingness of states to commit to long-term (often expensive) solutions make the negotiation of traditional international treaties and customary rule-making more difficult, and this has led to the development of law-making processes New and dynamic, mostly led by international organizations. The methodology of research is built on the concept that the first step in developing an overarching interpretation of the role of international organizations in the development of environmental law, is to abandon the idea of a weighty description of mechanisms in the categories of binding and non-binding (or soft vs. soft law), which focuses only on immediate effects. target, and predetermine the outcome of any analysis within its larger law-making characteristics. Instead, the article emphasizes the need to disregard the strict dichotomy of soft versus hard law when researching normative outcomes for international organizations allows for the collection and analysis of the widest variety of mechanisms and their individual characteristics. The article concludes that, only through this research, can new classification methods be recommended to be proposed for the "unlimited diversity" of the mechanisms of international organizations, and international lawyers can begin to devise new analytical mechanisms they need to examine the state of law at the institutional level in the current era.